If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6x + 3) + (-7x + 9) = 0 Reorder the terms: (3 + 6x) + (-7x + 9) = 0 Remove parenthesis around (3 + 6x) 3 + 6x + (-7x + 9) = 0 Reorder the terms: 3 + 6x + (9 + -7x) = 0 Remove parenthesis around (9 + -7x) 3 + 6x + 9 + -7x = 0 Reorder the terms: 3 + 9 + 6x + -7x = 0 Combine like terms: 3 + 9 = 12 12 + 6x + -7x = 0 Combine like terms: 6x + -7x = -1x 12 + -1x = 0 Solving 12 + -1x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + -1x = 0 + -12 Combine like terms: 12 + -12 = 0 0 + -1x = 0 + -12 -1x = 0 + -12 Combine like terms: 0 + -12 = -12 -1x = -12 Divide each side by '-1'. x = 12 Simplifying x = 12
| -5(r+2)=-98 | | 4/6x*x | | 4/5c=2/5 | | 10n+8=12 | | 18=m-7 | | 5x-y=x+13y | | -2x/7=4 | | 6x+12x-7=4(5x+4) | | (x+5)+[(x+40)5]=600 | | X+1(5)=60 | | 2d+-10=8 | | 78/-9= | | 9y+9=81 | | -5x+50=10 | | 2(2(a+4))=12 | | 78*-9= | | a-b^3+b-c^3+c-a^3= | | (86x+75y)=1000 | | 2(2(9+4))=12 | | 3n-8=76 | | 3n-69=0 | | (x-3)(x+4)=(x+6)2 | | (5x+7)+(-6+8)= | | 6x+18x=136x+17 | | 15n-3-14n-5=-2 | | 99-(5x+15)=5(x+8)+x | | -5(1+-3x)-4x=2(-7-3x)-8 | | X-30=-40 | | 15-3(x+1)=2(x+1) | | (x^-3y^2/x^5y^-2)^-1 | | t(a)=x^2+3x-1 | | -17-6=-38-p |